THE EFFECT OF WORK LIFE BALANCE, REWARD AND ORGANIZATIONAL COMMITMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Hasan, Muh; Sandi, Bobby (Universitas Muhammadiyah Tangerang, 2025)
The purpose of this study is to determine the Influence of Work-Life Balance, Rewards, and Organizational Commitment on Organizational Citizenship Behavior, both partially and simultaneously in PT Tri Sakti Purwosari Makmur. This study uses an associative method with a quantitative approach. The sampling was 100 people. Data collection techniques and tools are by questionnaire or questionnaire. Descriptive data analysis techniques are used to find out the picture of respondents' responses and data distribution, while inferential statistical analysis is for hypothesis testing. Data processing is assisted by Microsoft Excel software and SPSS version 26. The results show that Work Life Balance (X1), Reward (X2), and Organizational Commitment (X3) simultaneously have a positive and significant influence on Organizational Citizenship Behavior (Y). While the contribution of Work Life Balance (X1), Reward (X2), and Organizational Commitment (X3) with Organizational Citizenship Behavior (Y) was 49.5%, the remaining 50.5% was influenced by other variables (X) that were not studied in this study.